PERJANJIAN PRA NIKAH DALAM PRESPEKTIF HUKUM ISLAM - Elin Siswanti (Journal of Law ( Jurnal Ilmu Hukum ), 2021)
AbstractMarriage is a spiritual bond between man and woman as husband and wife to form a happy and eternal family based on the Godhead of the Almighty. Premarital agreements as regulated in Law Number 1 of 1974 concerning Marriage and Compilation of Islamic Law Inpres Number 1 of 1991 can be used as a legal tool to protect the rights and obligations of husband and wife when married life takes place. This study examines the existence of a prenuptial agreement according to Islamic law, the terms and procedures of a prenuptial agreement according to Islamic law, and the legal consequences arising from a prenuptial agreement according to Islamic law. This type of research used in this paper is a type of normative legal research using the law approach (statute approach).       The results of research and discussion determining the existence of pre-marital agreements in Islamic law are permissible. The existence of a prenuptial agreement is expected to assist husband and wife in increasing their understanding and awareness of their obligations and rights. The requirement to implement a prenuptial agreement in Islamic law is that the substance must not violate applicable legal and religious provisions. The procedure for implementing prenuptial agreements under Islamic Law is carried out in the Office of Religious Affairs in each region. The legal consequences arising from the prenuptial agreement according to Islamic law, namely the parties involved are bound and obliged to carry out the agreement.Keywords: Marriage agreement, Islamic law